Fabrication and characterization of Ag/PCDTBT/ZnO QD/ITO p-n junction based Photodetector - Singh A.P.; Upadhyay R.K.; Upadhyay D.C.; Jit S. (My University, 2025)
In this proposed paper, we exhibit a ZnO QDs based UV photodetector. By the colloidal synthesis route method, ZnO quantum dots were synthesized. Polymer PCDTBT behaves as P-type material for making a p-n junction diode. Finally, the study of optoelectronics characteristics of conventional device Ag/PCDTBT/ZnO Quantum Dot/ITO UV-photodetector at a 375 nm wavelength under the dark and light conditions and power density is $43\ \mu\mathrm{W}/\text{cm}^{2}$ of monochromator light source. It is found PCDTBT (p-type) and ZnO Quantum Dot (n-type) based conventional p-n junction photodetector has good electrical and optical performance in UV region. © 2020 IEEE.